The turnover and self management of irrigation institutions in developing countries: a discussion paper for a new program of the International Irrigation Management Institute - Vermillion, Douglas L. (International Irrigation Management Institute, 1991)
Discussion paper describing a new IIMI program for research, information and institutional support services concerning the turnover, privatization and self management of irrigation systems in developing countries.